High resolution XRF from IODP Site 323-U1342 - Tatsuhiko Sakamoto; Ana Christina Ravelo; Karla P Knudson (PANGAEA, 2021)
We present new high resolution records of elemental ratios from Integrated Ocean Drilling Program Expedition 323 Site U1342 in the Bering Sea. Sediment cores measured by non-disruptive XRF with the TATSCAN-F2 at the Japan Agency for Marine-Earth Technology in 2009. Si/Ti, Fe/Ti, and Fe/S ratios were calculated based on the mass measurements (at 0.50 cm resolution) of each of these elements. XRF measurements are likely not greatly affected by water attenuation, since precautions were taken to scan IODP cores after they had been opened and were no longer damp. Core tops (including the B/A laminated interval at this site) may be an exception for XRF reliability, as they are relatively soft and have greatest porosity and water content. In Knudson et al. (2021, Science Advances), Fe/Ti ratios were used to look at a possible change in iron source, and Si/Ti ratios were used as a proxy for biogenic opal deposition. This instrument, analytical methods, precision, and accuracy are described in detail in Sakamoto et al., 2006: T. Sakamoto, K. Kuroki, T. Sugawara, K. Aoike, K. Iijima, S. Sugisaki, Non-destructive X-ray fluorescence (XRF) core-imaging scanner, TATSCAN-F2. Sci. Drill 2, 37-39 (2006).